Research and Application of the Solving Method for Robotic Workspace - He Jiawei; Ping Xueliang; Li Zhaoyang; Jiang Yi (Jixie chuandong)
For the solution of the robotic workspace,on the basis of existing research methods,a new solution method which combines the advantage of Monte- Carlo method with Matlab simulation modeling capability is proposed. Based on Staubli TX60 L six axis serial robot,the workspace is respectively generated by using numerical method,the geometric mapping method and the proposed method,and comparison analysis is carried out,the results prove that this method need not to consider complex kinematics equation,and the accuracy high and computing speed fast.